EMERGENCY PREPAREDNESS FOR NURSING DALAM MENGHADAPI BENCANA DI KOMUNITAS - Rizki Wan Oktabina; Nuswatul Khaira; Desiana Desiana; Nurhayati Nurhayati; Wirda Hayati; Rahma Dalila Fitri; Putra Furiansyah (Poltekkes Kemenkes Aceh, 2022)
Nurses are the health profession with the most number when compared to other health professions. The competence of nurses in emergency preparedness is obtained through the educational process in higher education including knowledge, skills and attitudes in dealing with emergencies caused by disasters. The purpose of this study was to determine the perceptions of nursing students about emergency preparedness in disasters. This study uses a quantitative descriptive method using Scale of Perception of Disaster Preparedness among Nurses (SPDPN) questionnaire which consists of 3 (three) components, namely the preparation stage, intervention stage and post-disaster stage. The respondents of this study were 49 students of the Diploma Three Nursing Program in Banda Aceh. The results showed that the mean value for the Preparation Stage is 4.4, the Intervention Stage is 4 and the Post Disaster Stage is 4. The conclusion from this study is nursing students' perceptions for emergency nursing showed a positive perception. Beside it the learning process followed by the simulations can increase students' confidence in dealing with disasters.